The impact of innovations in the production of biologically valuable food products on supply chain management in the regional economy - I. L. Beilin; V. V. Khomenko; M. Sh Tagirov; R. I. Zinurova; K. R. Saubanov; N. M. Yakupova (International Journal of Supply Chain Management, 2020)
Abstract— The article shows a study of the role of supply chain management of innovative biologically valuable food products in the industrial development and economy of the region. The analysis of the process of updating the assortment of food products based on the introduction of innovative developments and production principles conducive to the release of a healthy diet product (innovative product) is presented. The main provisions of the concept of healthy food products, the category of “innovative food products” are analyzed. The article systematizes the definitions of the concept of “innovative product”. Based on the results of the study, features, functional properties and characteristic features of an innovative food product are determined. Based on the concept of “innovative food product”, the concepts of “new food product”, “improved food product”, and “modified food product” are formulated. A classification model of innovative food products is presented. Based on it, it is shown that the development, production and sale of an innovative food product two functions: economic and social. The study made it possible to formulate the main criteria that make it possible to attribute a food product to a group of innovative food products. The article describes the characteristics of an innovative food product, describes market and consumer properties. The author's definitions of concepts are given: “innovative food product”, “new food product”, “improved food product”, “modified food product”. A classification of innovative food products is proposed.